Folklora v vlogi označevanja vaških mej kot prostorskih vrzeli v onstranstvo. Primer Rodika Folklore in the Role of Demarcating the Village Limits as Spatial Openings into the »Other« World. The Case of Rodik - Hrobat, Katja (Studia mythologica Slavica, 2009)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article is part of a wider research into the perception of space in oral tradition. The qualification of space relies on the constitution of a border, which acts between the opposites it divides. The research focuses on the cadastral boundary, which is the main mediator between the worlds. In the case of Rodik it is defined by apparitions, sacrifices, and burials of creatures, which inhabit the world in-between (»bloody leg«, vedamec, snake, blacksmith, the impure dead, strangers, etc.).